2017
DOI: 10.1002/aoc.3702
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigation of dual pH‐ and temperature‐responsive behaviour of poly[2‐(dimethylamino)ethyl methacrylate]‐grafted gold nanoparticles

Abstract: Gold nanoparticles (AuNPs) were synthesized by reduction of chloroauric acid (HAuCl4) aqueous solution with hydrazine monohydrate. The AuNPs were immediately treated with cysteamine to obtain amine‐functionalized nanoparticles (Au‐NH2). The reaction of Au‐NH2 with epichlorohydrin and subsequent treatment with sodium hydroxide gave epoxidized AuNPs (Au‐EP). Then, thiol‐capped AuNPs (Au‐SH) were synthesized by reaction of Au‐EP with cysteamine. A ‘grafting to’ approach was utilized to graft bromine‐terminated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 43 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Gold nanoparticles (AuNPs) as non-toxic and biologically compatible nanoparticles have gotten increasing attention in different fields such as biomedicals [1], hybrid nanomaterials [2], etc. Also, Surface Plasmon resonance (SPR) as a unique optical property is conferred by the interaction of light with electrons on the surface of gold nanoparticles [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) as non-toxic and biologically compatible nanoparticles have gotten increasing attention in different fields such as biomedicals [1], hybrid nanomaterials [2], etc. Also, Surface Plasmon resonance (SPR) as a unique optical property is conferred by the interaction of light with electrons on the surface of gold nanoparticles [3].…”
Section: Introductionmentioning
confidence: 99%
“…). Also, the number‐averaged particle size ( D n ), weight‐averaged particle size ( D w ), and polydispersity index (PDI) are calculated according to the following equations: Dn=normalΣ1nniDinormalΣ1nni Dw=normalΣ1nniDi4normalΣ1nniDi3 PDI=DwDn where n i and D i are the number of particles and diameter respectively. According to the results, D n is 234.1, 167.7, and 267.0 nm for P1, P2, and P3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…72 However, there are limitations to this, as Mohammadi et al found a low mole-cular weight PDMAEMA brush layer (M n = 6280 g mol −1 ) could not exhibit temperature-responsive behaviour, regardless of pH. 74 It is important to note that there are many examples of other homopolymer stabilized NP systems that are likely to aggregate in response to pH and temperature changes, however, many publications focus on the stabilization of these systems.…”
Section: Temperature-and Ph-responsive Nanoparticle Aggregationmentioning
confidence: 99%